Study of intestinal protozoa infectio in the hospitalized patients diagnosed with diarrhoea in the Panembahan Senopati hospital - Nurlaili Farida Muhajir; Elsa Herdiana; Budi Mulyaningsih (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: Based on data from Bantul health profile 2012, diarrhoea was one of 10 major diseases in hospitalized patients in Panembahan Senopati Bantul Hospital. The presencetage of intestinal protozoan infection in the Panembahan Senopati Regional Public Hospital, Bantul, Yogyakarta is not known specifically.Objective: To determine the percentage of intestinal protozoa cases and the related factors in the hospitalized patient with diarrhoea in the Panembahan Senopati hospital.Methods: This study was conducted in September 2014-February 2015. The method used was observational analytic research.Results: The number of intestinal protozoan infection in the patient with diarrhoea is 37 people (45.1%) of the total 82 research subjects. Intestinal protozoa E. histolytica is found as many as 4 people (4.9%), E. coli 1 people (1.2%), Cryptosporidium 25 people (30.5%), Blastocystis 2 people (2.4%) and mix infection (E.histolytica & Cryptosporidium) 5 people (6.1%). Bivariate analysis showed the factors related to the infection with the significant relationship (p<0.05) are water sanitation facilities (p<0.000), toilet facilities (p<0.000), and garbage management (p<0.004). Multivariate analysis showed the sanitary water facilities and toilet facilities can give risk at once.Conclusion: The percentage of intestinal protozoan infection in the hospitalized patient with diarrhoea in Panembahan Senopati Hospital in the period of September 2014-February 2015 was 45%. Sanitary water facilities, toilet facilities, and garbage management facilities associated with the incidence of intestinal protozoan infection.